Delayed physiological acclimatization by African elephants following reintroduction - Jachowski, D. S.; Slotow, R.; Millspaugh, J. J. (Animal conservation, 2013)
Managers of reintroduced wildlife commonly encounter behavioral problems post‐release that have been linked to physiological condition and elevated stress hormone concentrations. However, there is uncertainty about the generality of a stress response among populations, factors influencing the intensity of the response and the amount of time needed to physiologically acclimatize. We evaluated the relationship of temporal, climatic and social factors to stress hormone concentrations in five African elephant (Loxodonta africana) populations following reintroduction. We determined fecal glucocorticoid metabolite concentrations (FGMs) in 1567 fecal samples collected from elephants reintroduced to five fenced reserves with differing reintroduction histories in South Africa during 2000–2006. Variation in FGMs across the five reserves was best explained by the number of years that elapsed since initial release. Compared with FGMs 1 year after release, FGMs were 10% lower 10 years after release and 40% lower 24 years after release. Across all reserves, FGMs were consistently highest in the dry season, although daily and monthly temperature and rainfall were not as important as other factors. FGMs did not vary solely in relationship to reserve size or elephant density. Our findings suggest that regardless of reintroduction site conditions, elephants and likely other species subject to reintroduction require an extended period of time to physiologically acclimatize to their new surroundings. Managers should prepare for prolonged behavioral and physiological consequences of long‐term elevated stress responses following reintroduction, such as restricted space use and aggressive behavior.